THE PROCESS OF POLITICIZING CLIMATE CHANGE AND PROMOTING SUSTAINABLE DEVELOPMENT DURING THE RISE OF NEOLIBERALISM - Carletti, Rafael (Revista Contraponto, 2025)
In this article, I seek to present some constituent elements of the process that resulted in the politicization of climate change and the idea of sustainable development during the period of institutionalization of neoliberalism. The application of Sustainable Development as a concept is relatively recent. Its first use appeared in the Brundtland Report in 1987 and was ratified years later at Rio-92. The term climate change, in turn, seemed to appear almost in the same period. Its first record appears in Resolution 43/53, the result of the 70th plenary meeting of the United Nations General Assembly in 1988. The appearance of these terms and the discussion surrounding their political meanings coincide with the implementation of neoliberalism at the beginning of the 1980s as a new ideological paradigm of capitalism. This work aims to understand the politicization of these two issues at that time, with neoliberal precepts as a political atmosphere. The methodological approach undertaken in this work is qualitative, and its main tools are the review of the bibliography on the topic and documentary analysis. The conclusion I present at the end of the article is that the oil companies, the main political and economic forces in the initial phase of neoliberalism, strategically incorporated the criticisms arising from the environmental movement and politicized, from a neoliberal perspective, the discussions around climate change and the construction of the sustainable development. https://doi.org/10.5935/2358-3541.2024140482-pt